Cytoskeletal prestress regulates nuclear shape and stiffness in cardiac myocytes. (November 2015) - Lee, Hyungsuk; Adams, William J; Alford, Patrick W; McCain, Megan L; Feinberg, Adam W; Sheehy, Sean P; Goss, Josue A; Parker, Kevin Kit
Mechanical stresses on the myocyte nucleus have been associated with several diseases and potentially transduce mechanical stimuli into cellular responses. Although a number of physical links between the nuclear envelope and cytoplasmic filaments have been identified, previous studies have focused on the mechanical properties of individual components of the nucleus, such as the nuclear envelope and lamin network. The mechanical interaction between the cytoskeleton and chromatin on nuclear deformability remains elusive. Here, we investigated how cytoskeletal and chromatin structures influence nuclear mechanics in cardiac myocytes. Rapid decondensation of chromatin and rupture of the nuclear membrane caused a sudden expansion of DNA, a consequence of prestress exerted on the nucleus. To characterize the prestress exerted on the nucleus, we measured the shape and the stiffness of isolated nuclei and nuclei in living myocytes during disruption of cytoskeletal, myofibrillar, and chromatin structure. We found that the nucleus in myocytes is subject to both tensional and compressional prestress and its deformability is determined by a balance of those opposing forces. By developing a computational model of the prestressed nucleus, we showed that cytoskeletal and chromatin prestresses create vulnerability in the nuclear envelope. Our studies suggest the cytoskeletal–nuclear–chromatin interconnectivity may play an important role in mechanics of myocyte contraction and in the development of laminopathies by lamin mutations.